Mitochondrial activator BGP-15 protects sperm quality against oxidative damage and improves embryo developmental competence - Gonzalez, Macarena B; McPherson, Nicole O; Connaughton, Haley S; Winstanley, Yasmyn E; Kennedy, David T; Campugan, Carl A; Febbraio, Mark A; Barry, Michael; Rose, Ryan D; Robker, Rebecca L (F&S Science (Online), 2025)
To study the efficacy of mitochondrial activator BGP-15 to preserve sperm quality and competence against cellular damage. Spermatozoa from mice or humans were treated in vitro with BGP-15, and sperm quality markers were assessed. Spermatozoa from young (8-12 weeks old) or reproductively old (>14 months old) mice were treated with BGP-15 for 1 hour and assessed for sperm quality and preimplantation embryo development after in vitro fertilization. The safety of BGP-15 on offspring outcomes was assessed through embryo transfers. In parallel studies, spermatozoa from healthy (not infertile) men were incubated in hydrogen peroxide, to induce oxidative stress, plus increasing doses of BGP-15, and sperm quality was evaluated. Spermatozoa from patients undergoing assisted reproductive technology (ART) treatment were incubated in the optimized dose of BGP-15 for 30 minutes, and sperm quality was assessed. C57BL/6 mice (N = 4-15 per group) for sperm quality and embryo development. CBAF1 mice (n = 6 per group) produced embryos for transfer. Human spermatozoa were from men with no infertility diagnosis (n = 14-20) or men undergoing ART (n = 33) at a local fertility clinic. Mouse spermatozoa were treated with 10-μM BGP-15. Human spermatozoa were treated with BGP-15 at doses from 1 to 100 μM. Sperm quality measures (mouse and human) included motility, mitochondrial membrane potential (JC-1 dye), deoxyribonucleic acid (DNA) fragmentation ("HALO" assay), and DNA oxidation (8-oxoguanine immunodetection). Mouse embryo and offspring measures included on-time development after in vitro fertilization, morphokinetic analysis, and blastocyst inner cell mass and trophectoderm cell number, and growth and development from birth to 21 days postnatally. BGP-15 increased sperm motility and mitochondrial membrane potential and decreased DNA oxidation in old mice. BGP-15 improved on-time development of 2-cell and blastocyst embryos and increased the inner cell mass blastomere number. Embryos from BGP-15-treated mouse spermatozoa produced normal offspring. In human spermatozoa subjected to in vitro oxidative stress, BGP-15 increased motility by 45% and prevented DNA fragmentation (by 45%) and oxidative damage (by 60%). In spermatozoa from men attending a fertility clinic, BGP-15 increased motility by 12% and reduced both DNA oxidation and fragmentation by >20%. BGP-15 protects sperm against cellular damage and has the potential to improve ART outcomes.